Transcriptome Comparison between Resistant and Susceptible Soybean Cultivars in Response to Inoculation of Phytophthora sojae - Sangrea Shim; In-Jeong Kang; Hee Jin You; Hangil Kim; Sungwoo Lee (The Plant Pathology Journal)
Phytophthora root and stem rot, caused by Phytophthora sojae, considerably reduces soybean yield worldwide. Our previous study identified two genomic regions on chromosome 18 (2.1–2.6 and 53.1–53.3 Mbp) that confer resistance to the P. sojae isolate 2457, through linkage analysis using progenies derived from the Daepung × Socheong2 population. These two regions contained 51 and 19 annotated genes, respectively. However, the specific gene responsible for resistance to P. sojae isolate 2457 has yet to be identified. In this study, we performed a comparative transcriptomic analysis of Socheong2 and Daepung, two Korean soybean varieties identified as resistant and susceptible to P. sojae isolate 2457, respectively. RNA sequencing was conducted on tissue samples collected at 0, 6, and 12 hours after inoculation (HAI), and significant differences in the expression of defense-related genes were observed across time points and between the two cultivars. Genes associated with the jasmonic acid, salicylic acid, ethylene, and systemic acquired resistance pathways were upregulated in both cultivars at 6 and 12 HAI compared to 0 HAI, with these biological processes were more strongly upregulated in Socheong2 compared to Daepung at 6 and 12 HAI. A comparison of differentially expressed genes (DEGs) and candidate genes within the previously identified QTL regions revealed an ortholog of the HS1 PRO-1 2 gene from Arabidopsis thaliana among the upregulated DEGs in Socheong2, particularly at 12 HAI compared to 0 HAI. This study will aid in targeted breeding efforts to develop soybean varieties with improved resistance to P. sojae.